Full blood count dynamics in immunologically naïve individuals with mild COVID-19: A prospective community cohort study - Seran Hakki; Sean Nevin; Emily Conibear; Kieran J. Madon; Joe Fenn; Jakob Jonnerby; Nieves Derqui; Aleksandra Koycheva; Rhia Kundu; Hamish Houston; Timesh D. Pillay; Alexandra L. Kondratiuk; et al. (PLoS ONE, 2026)
Purpose Full blood count (FBC) provides a range of cellular haematological parameters and serves as a routinely available basic immune profile. While FBC has been widely used to monitor moderate-to-severe COVID-19 in hospitalised settings, its temporal dynamics in mild, community-managed cases remain poorly characterised, despite these constituting the majority of global infections. Methods In a prospective cohort study, we tracked the cellular haematological profiles of 93 recently exposed, immunologically naïve individuals with mild COVID-19 and no underlying co-morbidities, recruited to the Integrated Network for Surveillance, Trials and Investigations into COVID-19 Transmission (INSTINCT) study. Blood samples were collected on D0, D7, D14 and D28 and subsequently aligned to infection-timepoints based on the day of first detected PCR positivity, and analysed using mixed-effects models. Results Over 30% of cases exhibited transient, clinically defined neutropenia (mean (95% CI): First PCR-Positive (FP) 2.47x10 9 /L (2.26–2.68) vs convalescence 3.34 x10 9 /L (2.98–3.7); p = 0.0013). Over 20% exhibited lymphopenia (FP 1.38x10 9 /L (1.28–1.48) vs convalescence 1.79x10 9 /L (1.79–2.01); p = 0.0013). Additionally, we observed a notable elevation in platelet count, peaking approximately two weeks after initial infection (mean (95% CI): FP + 14 283x10 9 /L (254–311) vs convalescence 237x10 9 /L (222–252); p = 0.0013). Conclusions Transient neutropenia and lymphopenia occurred in approximately one-third and one-fifth of mild COVID-19 cases, respectively, and were followed by a delayed increase in platelet count. This study provides a descriptive, prospective dataset of full blood count parameters spanning early infection to convalescence in immunologically naïve individuals with mild SARS-CoV-2 infection. These data may support mathematical modelling of within-host cellular haematological dynamics and have potential clinical relevance for understanding typical trajectories of routine blood parameters during mild disease.